Advertisement and Gender: A Critical Discourse Analysis - خنفر، عادل مالك (جامعة البصرة - كلية الآداب, 2017)
تحاول الدراسة تحليل الخطاب النقدي للجنس في بعض الإعلانات المختارة. ومن المفترض أن الرجال والنساء يتم إدخالها بشكل مختلف في هذه الإعلانات وتستخدم النساء كأدوات جنسية لغرض مقنع لجدب الجمهور المستهدف. في الجانب النظري للدراسة، هناك مناقشة لتعريف ووظائف الهيئة، والإعلانات، ونوع الخطاب المستخدم في الإعلان بالإضافة إلى إبراز الدور الجنساني والقولبة في الإعلان. نتائج التحليل تتحقق من فرضية الدراسة إلى حد كبير. الاستنتاج الرئيسي هو أن الخطاب الإعلاني ليس محايدا، بل على العكس من ذلك، فإنه منحازة إلى حد كبير لتفوق دور الرجل في المجتمع. وتعترض المرأة على الاستئناف الجنسي، كما أن عنوان الجنس في الإعلانات مباشر ومفتوح.
The Study attempts a Critical Discourse Analysis ( CDA) of gender in some selected advertisements . It is hypothesized that men and women are differently introduced in these advertisements and women are used as sex objects for the persuasive purpose of attracting the targeted audience . In the theoretical side of the study , there is a discussion of the definition and functions of CDA , advertising , and the kind of discourse employed in advertising in addition to highlighting gender role and stereotyping in advertising . Findings of the analysis verify the hypothesis of the study to a large extent . The main conclusion is that advertising discourse is not neutral , and on the contrary , it is very largely biased to the superiority of the role of men in society . Women are objectified for sex appeal and the sex address in the advertisements is direct and open .
Keywords: الإعلانات النقدية -- الخطاب الإعلانى